2010
DOI: 10.3406/ecmed.2010.1362
|View full text |Cite
|
Sign up to set email alerts
|

Évolution des caractéristiques écologiques le long d’un gradient de dégradation édaphique dans les parcours du sud tunisien

Abstract: This study was carried out in the region of Ouled Chehida located in the Tunisian south. It aims at assessing the impact of the exploitation (grazing) on the dynamic of plant cover of various types of rangelands of the region. The variations of the cover rate, the species density, specific diversity as well as the grazing value both in grazed and rested rangelands were observed. The results of this study show that all observed parameters vary enormously from one rangeland type to another according to the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…However, this response varied with soil and vegetation type. These results corroborate the findings of other studies for arid ecosystems [56,57]. In southern Tunisia, Floret and Pontanier [58] explained that rainfall and soil type were decisive factors and higher response of vegetation and soil moisture levels were observed in deep sandy soils compared to limestone soils.…”
Section: Discussionsupporting
confidence: 91%
“…However, this response varied with soil and vegetation type. These results corroborate the findings of other studies for arid ecosystems [56,57]. In southern Tunisia, Floret and Pontanier [58] explained that rainfall and soil type were decisive factors and higher response of vegetation and soil moisture levels were observed in deep sandy soils compared to limestone soils.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, thorny and spiny plants (e.g. Astragalus armatus ) were less selected by the addax, consistent with what has been reported for several ruminant species (Gamoun et al 2010). Other plants were not selected, such as Oudeneya africana , because they contain an inhibitor of rumen microbial fermentation (tannins) that limits their digestibility (Hammami and Fliss 2010).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study in the area has indicated that CG has a wide range of effects on the composition, diversity, and rangelands production (Gamoun, Chaieb, et al 2010;Gamoun 2014). Livestock grazing has caused a severe degradation of vegetation both directly (by eating it) and indirectly (trampling) (Gamoun, Tarhouni, et al 2010).…”
Section: Discussionmentioning
confidence: 99%